Tinjauan Yuridis Hak Pasien Dalam Perspektif Hukum Perdata - Klau, Ricardo Goncalves; Ervin Novara Jaya, Andi; Saiful Fahmi, Muhammad; Majid, Ilham; Ayu Utami, Gusti (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2025)
Patient rights in the context of civil law become an important issue in the relationship between patients and health workers as a form of engagement based on a therapeutic contract. This study aims to examine patients' rights from a civil law perspective, focusing on the aspect of legal responsibility in the contractual relationship between patients and health care providers. This study refers to the principles in the Civil Code as well as relevant regulations, such as Law No. 17 of 2023 on Health. The study uses a normative juridical method with a conceptual approach and case analysis to identify the implementation of patient rights, such as the right to proper medical services, the right to obtain information, and the right to sue in the event of negligence or violation of rights. The results show that the legal relationship between patients and health workers places patients as parties who have the right to demand the fulfillment of health workers' obligations, including the right to obtain compensation for losses arising from medical negligence. However, the implementation of patient rights in the perspective of civil law often faces obstacles, such as inequality of legal knowledge between patients and health workers, complex evidentiary processes, and the unpreparedness of the community in understanding their legal rights. This study recommends strengthening legal education for the community, providing more inclusive access to justice, and strict law enforcement to ensure the protection of patients' rights within the framework of civil law.